Ability of basic school teachers in developing 2013 curriculum based learning administration devices in elementary school - Anggaraenir, Yoseu; Fitria, Happy; Wahidy, Achmad (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine and describe the ability of elementary school teachers in preparing the 2013 curriculum-based learning administration tool in SD Negeri 3 Air Kumbang sub-district. This type of research is descriptive qualitative research. Data collection tools use documentation, interviews, observation and literature review. The data analysis technique used qualitative descriptive analysis techniques which consisted of data collection, data reduction, data presentation, and conclusion and verification. The results of this study indicate that the teacher's ability to arrange learning administration tools in SD Negeri 3 Air Kumbang District, which is carried out through the process, strategic planning, strategy implementation and strategy evaluation have been going according to what was expected from the start so that there is the ability of the teacher to compile this school administration tool. then it can help in improving the quality of learning at SD Negeri 3 Air Kumbang District. It remains only to how the teacher and all school members maintain the quality of learning that has been obtained by SD Negeri 3 Air Kumbang District.